2007
DOI: 10.1111/j.1365-2672.2007.03441.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cranberry phenolics on glucan synthesis by glucosyltransferases and Streptococcus mutans acidogenicity

Abstract: Aims:  To investigate the influence of several phenolic compounds isolated from cranberry fruit (Vaccinium macrocarpon) on some of the virulence properties of Streptococcus mutans associated with glucan synthesis and acidogenicity. Methods and Results:  Individual phenolic acids, flavonols and proanthocyanidins were isolated by semi‐preparative high‐performance liquid chromatography from fresh cranberry fruit. Flavonols and proanthocyanidins (at 500 μmol l−1) moderately inhibited the activity of surface‐adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
164
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(171 citation statements)
references
References 37 publications
1
164
0
6
Order By: Relevance
“…Our polyphenol fraction sample contained 34% flavonol, including catechins and primary components such as proanthocyanidins. Gregoire et al 3) identified the bioactive constituents in cranberry against S. mutans using highly purified isolated compounds, and showed the combined effects of specific flavonol and proanthocyanidins on glucan synthesis and acidogenicity. They suggested that the biological activity of cranberry extracts resulted from the complex mixture of flavonoids rather than a single active compound.…”
Section: Discussionmentioning
confidence: 99%
“…Our polyphenol fraction sample contained 34% flavonol, including catechins and primary components such as proanthocyanidins. Gregoire et al 3) identified the bioactive constituents in cranberry against S. mutans using highly purified isolated compounds, and showed the combined effects of specific flavonol and proanthocyanidins on glucan synthesis and acidogenicity. They suggested that the biological activity of cranberry extracts resulted from the complex mixture of flavonoids rather than a single active compound.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the side effects of root canal irrigants like sodium hypochlorite, chlorhexidine previous studies have investigated the effects of natural compounds mainly extracted from teas, cranberrie or propolis for antimicrobial purpose [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Cranberry juice and hydroalcoholic crude extracts also prevent bacterial adherence to apatitic surfaces and reduce the formation of biofilms by oral bacteria in vitro [Weiss et al, 2002;Steinberg et al, 2002;Yamanaka et al, 2004;Koo et al, 2006;Duarte et al, 2006]. Recently, we have shown that topical applications of PAC-enriched extract significantly reduced the formation, insoluble polysaccharide content and acidogenicity of S. mutans biofilms in vitro without displaying bactericidal effects [Duarte et al, 2006;Gregoire et al, 2007]. The biological actions were attributed to the combined inhibitory effects of PAC on the activity of surfaceadsorbed GtfB and GtfC, and on bacterial glycolysis [Duarte et al, 2006;Gregoire et al, 2007].…”
mentioning
confidence: 99%